Characteristics and outcomes of hospitalised older patients with chronic kidney disease and COVID‐19: A multicenter nationwide controlled study. Issue 9 (17th June 2021) - Ozturk, Savas; Turgutalp, Kenan; Arici, Mustafa; Gok, Mahmut; Islam, Mahmud; Altiparmak, Mehmet Riza; Aydin, Zeki; Doner, Baris; Eren, Necmi; Sengul, Erkan; Karadag, Serhat; Ozler, Tuba Elif; et al.
Abstract: Objective: Older adults with co‐morbidities have been reported to be at higher risk for adverse outcomes of coronavirus disease 2019 (COVID‐19). The characteristics of COVID‐19 in older patients and its clinical outcomes in different kidney disease groups are not well known. Methods: Data were retrieved from a national multicentric database supported by Turkish Society of Nephrology, which consists of retrospectively collected data between 17 April 2020 and 31 December 2020. Hospitalised patients aged 18 years or older with confirmed COVID‐19 diagnosis suffering from stage 3‐5 chronic kidney disease (CKD) or on maintenance haemodialysis (HD) treatment were included in the database. Non‐uraemic hospitalised patients with COVID‐19 were also included as the control group. Results: We included 879 patients [388 (44.1%) female, median age: 63 (IQR: 50‐73) years]. The percentage of older patients in the CKD group was 68.8% (n = 188/273), in the HD group was 49.0% (n = 150/306) and in the control group was 30.4% (n = 70/300). Co‐morbidities were higher in the CKD and HD groups. The rate of presentation with severe‐critical disease was higher in the older CKD and HD groups (43.6%, 55.3% and 16.1%, respectively). Among older patients, the intensive care unit (ICU) admission rate was significantly higher in the CKD and HD groups than in the control group (38.8%, 37.3% and 15.7%, respectively). In‐hospital mortality or death and/or ICU admission rates in the older group were significantly higher in the CKD (29.3% and 39.4%) and HD groups (26.7% and 30.1%) compared with the control group (8.6% and 17.1%). In the multivariate analysis, in‐hospital mortality rates in CKD and HD groups were higher than control group [hazard ratio (HR): 4.33 (95% confidence interval [CI]: 1.53‐12.26) and HR: 3.09 (95% CI: 1.04‐9.17), respectively]. Conclusion: Among older COVID‐19 patients, in‐hospital mortality is significantly higher in those with stage 3‐5 CKD and on maintenance HD than older patients without CKD regardless of demographic characteristics, co‐morbidities, clinical and laboratory data on admission.